PENGARUH KEPUASAN PELANGGAN TERHADAP PEMBELIAN PRODUK PADA E- COMMERCE - Aisya Badria Rosita; Dian Sudiantini, Angelita Ageng Arsabita, Eka Diniarti, Khalida Dwi Maylani, Ninik Nuraini (Jurnal Ekonomi dan Bisnis, 2024)
E-Commerce has become an integral part of everyday life, facilitating the purchase of products online. Customer satisfaction is a key factor influencing the success of e- commerce. This research aims to influence customer satisfaction in the context of purchasing products through e-commerce platforms. The survey method is used to collect data from respondents who use e-commerce. The results of the analysis show that product quality, responsive customer service, delivery speed, and brand trust have a significant positive impact on customer satisfaction. However, the price of the product does not have a significant eflect on customer satisfaction. The implication of this study is the importance of focusing on improving product quality, eflective customer service, and brand trust to improve customer satisfaction and strengthen e-commerce performance. This research provides valuable insights for e-commerce business owners to improve their strategies in managing customer relationships and strengthen their market share in the digital realm.